Coupled transport of Pb2+ through tri‐n‐octylamine‐xylene‐polypropylene supported liquid membranes. (13th July 2012) - ur Rehman, Saeed; Akhtar, Gul; Chaudry, M. Ashraf
Abstract Transport of Pb2+ was carried from acidic solution into alkaline stripping phase through tri‐n‐octylamine‐xylene‐polypropylene supported liquid membrane. The transport of Pb2+ through the membrane was studied by varying the concentration of Pb2+ and HNO3 in feed solution, NaOH concentration in strip solution and TOA concentration in membrane phase. The flux data obtained has been used to study the stoichiometry of complex Pb(NO3)n+2(HNR3)n. The supported liquid membrane (SLM) has been found stable for 10 runs with 24 h between each run. This SLM has been used effectively to extract lead ions along with chromium, copper and zinc ions from aqueous acidic leached solution of paint and industrial effluents. © 2012 Canadian Society for Chemical Engineering